Familial cataracts: profile of patients and their families at a child eye care tertiary facility in a developing country (2023)
Purpose: The aim of this study is to describe the clinical profile, pedigree charting, and management of children with familial cataracts at a child eye health tertiary facility in southwest Nigeria. Methods: The clinical records of children ≤16 years diagnosed with familial cataracts at the Pediatric Ophthalmology Clinic, University College Hospital Ibadan (Ibadan, Nigeria) from January 1, 2015, to December 31, 2019, were retrospectively reviewed. Information on demographic data, family history, visual acuity, mean refractive error (spherical equivalent), and surgical management was retrieved. Results: The study included 38 participants with familial cataract. The mean age at presentation was 6.30 ± 3.68 years, with a range of 7 months to 13 years. Twenty-five patients (65.8%) were male. All patients had bilateral involvement. The mean duration from onset of symptoms to presentation at the hospital was 3.71 ± 3.20 years, with a range of 3 months to 13 years. In 16 of the 17 pedigree charts obtained, at least one individual was affected in each generation. The most common cataract morphology was cerulean cataract, observed in 21 eyes (27.6%). The most common ocular comorbidity was nystagmus which was observed in seven patients (18.4%). Sixty-seven eyes of 35 children underwent surgery within the period of the study. The proportion of eyes that had best-corrected visual acuity ≥6 / 18 before surgery was 9.1%; this proportion had increased to 52.7% at the last postoperative visit. Conclusions: Autosomal dominant inheritance appears to be the major pattern among our patients with familial cataract. The most common morphological type found in this cohort was cerulean cataract. Genetic testing and counseling services are vital for the management of families with childhood cataract.